ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (STUDI PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN LAMONGAN) - Evinta Hogi Pratama; Novi Darmayanti (Fakultas Ekonomi, 2023)
This study to determine how much influence Human Resource Competence, Implementation of Government Accounting Standards and Internal Control Systems have on the Quality of Local Government Financial Reports. The population in this study is the Regional Financial and Asset Management Agency of Lamongan Regency. The sampling method used in this research is saturated sampling. Data collection techniques in this study by distributing questionnaires to 58 respondents. The data were analyzed using the multiple linear regression method and processed with the SPSS Version 28 program. Based on the results of the study, it was concluded that the Competence of Human Resources, Internal Control Systems partially positive and significant effect on the quality of local government financial reports but for the variable Application of Accounting Standards The government has no positive and significant effect on the quality of local government financial reports. Human Resource Competence, Implementation of Government Accounting Standards and Internal Control Systems simultaneously have a positive effect on the Quality of Local Government Financial Reports.